Hierarchical Nanocauliflower Chemical Assembly Composed of Copper Oxide and Single-Walled Carbon Nanotubes for Enhanced Photocatalytic Dye Degradation - Kamal Prasad Sapkota; Md. Akherul Islam; Md. Abu Hanif; Jeasmin Akter; Insup Lee; Jae Ryang Hahn (Nanomaterials, 2021)
We present the fabrication and proficient photocatalytic performance of a series of heterojunction nanocomposites with cauliflower-like architecture synthesized from copper(II) oxide (CuO) nanocrystals and carbon nanotubes with single walls (SWCNTs). These unique photocatalysts were constructed via simplistic recrystallization succeeded by calcination and were labeled as CuOSC-1, CuOSC-2, and CuOSC-3 (representing the components; CuO and SC for SWCNTs, and the calcination time in hours). The photocatalytic potency of the fabricated nanocomposites was investigated on the basis of their capability to decompose methylene blue (MB) dye under visible-light irradiation. Every as-synthesized nanocomposite was effective photocatalyst for the photodecomposition of an MB solution. Moreover, CuOSC-3 exhibited the best photocatalytic activity, with 96% degradation of the visible-light irradiated MB solution in 2 h. Pure CuO nanocrystals generated through the same route and pure SWCNTs were used as controls, where the photocatalytic actions of the nanocomposite samples were found to be remarkably better than that of either the pure CuO or the pure SWCNTs. The recycling proficiency of the photocatalysts was also explored; the results disclosed that the samples could be applied for five cycles without exhibiting a notable change in photocatalytic performance or morphology.